Effective adenoviral transfer of IkappaBalpha into human fibroblasts and chondrosarcoma cells reveals that the induction of matrix metalloproteinases and proinflammatory cytokines is nuclear factor-kappaB dependent. - Bondeson, J; Brennan, F; Foxwell, B; Feldmann, M (2000)
OBJECTIVE: To determine whether, in human fibroblasts and chondrosarcoma cells, the regulation of interleukins (IL)-6, 8, and 11 and matrix metalloproteinases (MMP)-1, 3, and 13, and their tissue inhibitor TIMP-1, depends on the transcription factor nuclear factor-kappaB (NF-kappaB). METHODS: Fibroblasts and chondrosarcoma cells were effectively infected with an adenovirus encoding human IkappaBalpha, and inhibition of NF-kappaB function was observed. The induction of MMP and IL-6, 8, and 11 by various stimuli was assessed by ELISA. RESULTS: The induction of IL-6 and IL-8 clearly depended on NF-kappaB in both fibroblasts and chondrosarcoma cells, irrespective of stimulus, but IkappaBalpha overexpression had little effect on IL-11. MMP-1, -3, and -13 were also inhibited, but TIMP-1 was unaffected. CONCLUSION: NF-kappaB appears to play an important and selective role in MMP induction in human fibroblasts and chondrosarcoma cells. This suggests there are NF-kappaB dependent mechanisms of cartilage destruction in rheumatoid arthritis, and supports the concept that there are similarities in the regulation of inflammatory and destructive pathways in that disease.